Mathematics for Computer Science I (Linear Algebra) - M.A., Burhanuddin (FTMK, 2007)
This lab module aimed primarily for students who is taking subject BACS 1253 from UTeM, BACS 1253 - Mathematics for Computer Science I. Each chapter begins with a brief learning outcome for the students to acquire in the classes. Then the chapter starts with the theories behind that comprises the definition of the theorems. Next it will be followed by a step-by-step exercise and example of the problems. Lastly, the chapter end with a numbers of questions for student’s self study.